2008
DOI: 10.1111/j.1945-1474.2008.tb01170.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Prophylactic Perioperative Antibiotic Utilization in a Hospital System

Abstract: The Centers for Medicare and Medicaid Services and the Centers for Disease Control and Prevention launched the Surgical Infection Prevention Project in 2002. The groups developed performance measures regarding perioperative antibiotic use to prevent surgical site infections. Other organizations have since adopted these measures. Spectrum Health, a not-for-profit health system in western Michigan with seven hospitals, more than 140 service sites, and a 565,000-member health insurance plan, formed an interdiscip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…59,60,61 Enabling interventions were found to “increase the means and reduce barriers to enhance capability and opportunity” 58 and were considered the most effective intervention type compared with restrictions of use by expert approval. 62 Examples of enabling interventions include audit and feedback, 59,60,61,63,64,65 educational outreach, 63,66 and clinical decision support systems. 67,68,69…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59,60,61 Enabling interventions were found to “increase the means and reduce barriers to enhance capability and opportunity” 58 and were considered the most effective intervention type compared with restrictions of use by expert approval. 62 Examples of enabling interventions include audit and feedback, 59,60,61,63,64,65 educational outreach, 63,66 and clinical decision support systems. 67,68,69…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review by Davey et al 58 [59][60][61][63][64][65] educational outreach, 63,66 and clinical decision support systems. [67][68][69] Adoption of clinical decision support systems may improve evidence-based antimicrobial use.…”
Section: Ams Interventionsmentioning
confidence: 99%
“…4 Surgical site infections are one of the most investigated issues in healthcare. [5][6][7] Some of the most common tools for reducing the risk of infection in healthcare are surveillance, epidemiological guidelines, procedures, and training of healthcare personnel. 4,8 The University Hospital "Federico II" of Naples (Italy) currently adopts, in line with the recommendations suggested by the literature as well as national and regional legislation, an integrated strategy of actions to monitor and prevent HAIs.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the monitoring and prevention of HAIs represents a priority for the healthcare sector, and reducing the incidence of HAIs is a quality indicator of the services provided . Surgical site infections are one of the most investigated issues in healthcare …”
Section: Introductionmentioning
confidence: 99%
“…In Europe, losses include an estimated €7 billion in direct costs alone and an extra 16 million hospital stay days; in the USA, the corresponding cost is $6.5 billion. 5 Healthcare-associated infections are therefore widely investigated in healthcare, [8][9][10] and research has revealed correlations between certain viral infections and bacteria in various pathologies. 11,12 Several factors cause HAIs, some of which are related to prolonged and inappropriate use of invasive devices and antibiotics, insufficient application of standard and isolation precautions, inadequate environmental hygiene, poor infrastructure, insufficient equipment, lack of standardized procedures, and the absence of local and national guidelines and policies.…”
mentioning
confidence: 99%